ISLAMIC MICROFINANCE AND POVERTY ALLEVIATION: A STUDY OF SHARIAH-BASED LENDING PRACTICES IN INDONESIA - Syarifuddin Syarifuddin; Nadia Wiliams; Michel Sylvain (Sharia Oikonomia Law Journal, 2025)
Islamic microfinance offers an alternative, ethical approach to financial inclusion, especially for marginalized populations traditionally excluded from conventional banking systems. In the Caribbean context, where economic disparities persist and Muslim minorities face systemic challenges, the potential for Islamic microfinance remains underexplored. This study investigates the role of Islamic microfinance in empowering marginalized Muslim and non-Muslim communities in Trinidad and Tobago. The research employs a qualitative case study approach, combining semi-structured interviews with microfinance practitioners, community leaders, and beneficiaries across three local institutions offering Shariah-compliant financial services. Findings reveal that Islamic microfinance models—particularly those based on qard al-hasan (benevolent loans) and murabaha (cost-plus financing)—are perceived as more culturally inclusive, trust-based, and ethically appealing than their conventional counterparts. However, institutional limitations, lack of regulatory clarity, and insufficient awareness among beneficiaries restrict broader scalability. The study concludes that Islamic microfinance, when locally adapted and supported by policy and education, holds significant promise for advancing socio-economic empowerment in Caribbean plural societies. This case contributes to the growing discourse on Islamic social finance in non-Muslim-majority regions and highlights its relevance in fostering inclusive development models.